To the question of control of servomotors of automatic welding unit designed for welding of large-sized tanks of launch vehicles - A. A. Ibatullin; E. S. Gebel; V. N. Gudinov (Омский научный вестник)
The article discusses the process of servo drive control during welding using the SB-2000 welding unit. On the basis of technological process of welding of large-size tanks of launch vehicles power plants for modernization are revealed. A structural solution is proposed for process control and synchronization of electric drives with the use of servo motors. A technical solution and block diagram of the servo drive control algorithm are developed using the SINAMICS S120 modules of the SIEMENS company